(untitled) (Annals of Medical Research, 2021)
Aim: Colorectal cancers are common in the world and many factors play a role. MTHFR (methylenetetrahydrofolate reductase) gene polymorphisms cause a predisposition to cancer formation. C677T polymorphism is the most common among these. To evaluate the role of MTHFR polymorphisms in colorectal carcinogenesis, we examined the associations between MTHFR mutations, homocysteine levels, plasma folate levels and colorectal cancer risk. Materials and Methods: During two years period, 101 naive colorectal cancer cases and 95 controls were enrolled to the study and groups were matched for age, sex and smoking. The presence of the mutation was determined by real-time PCR amplification of genomic DNA using Light. Results: Although only 1 of the cancer patients was homozygous mutant Val/Val, this mutation was present in 10.5% of the control group and this difference was statistically significant (p<0.05). We observed a significant increased risk of colorectal cancer (OR, 0.04; 95% CI, 0.005-0.304) among those with low plasma folate levels (≤3 ng/ml) compared to subjects with adequate levels. However, in both case and control groups mean folate levels were high (10.3 and 10.7 ng/ml, respectively). Homocysteine levels were significantly higher in patients with colorectal cancer compared to healthy volunteers (p <0.05). Conclusion: The data in our study suggested that the MTHFR val/val mutation did not cause a predisposition to cancer development. The presence of a polymorphism other than val/val mutation in the MTHFR enzyme suggests that it may be associated with elevated levels of homocysteine and low folate in cancer patients.